2013
DOI: 10.1590/s0001-37652013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Stonemeal of amazon soils with sediments from reservoirs: a case study of remineralization of the tucuruí degraded land for agroforest reclamation

Abstract: This study suggests the employment of accumulated sediments in the reservoir of Tucuruí (Pará /Brazil) to remineralize the surrounding degraded soils. The approach was based on the principles of stonemeal technology. It suggests that the soil can be rejuvenated by crushed rocks rich in macro and micronutrients. Removal of the sediments for agricultural use will bring benefits to family farmers and increase the life cycle of the reservoir and, therefore, energy generation. Geochemical data on retained sediments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 4 publications
0
6
0
10
Order By: Relevance
“…While evaluating an agroforestry system, Theodoro et al (2013) used sediments that accumulated in the Tucuruí water reservoir (Pará, Brazil) to remineralize degraded soils of its surroundings together with crushed rock with or without the addition of NPK and organic compost. Their studies showed that greater plant growth and productivity were obtained in the portions where a mixture of sludge, ground rock and organic compost was added.…”
Section: Resultsmentioning
confidence: 99%
“…While evaluating an agroforestry system, Theodoro et al (2013) used sediments that accumulated in the Tucuruí water reservoir (Pará, Brazil) to remineralize degraded soils of its surroundings together with crushed rock with or without the addition of NPK and organic compost. Their studies showed that greater plant growth and productivity were obtained in the portions where a mixture of sludge, ground rock and organic compost was added.…”
Section: Resultsmentioning
confidence: 99%
“…É importante destacar que a disponibilização ou solubilização dos nutrientes derivados desses materiais é mais lenta do que os fertilizantes químicos solúveis, mas está aparente desvantagem é compensada com uma disponibilização por períodos de tempo mais longos (slow-release). Por isso, são considerados "fertilizantes inteligentes" (Theodoro, et al, 2013).…”
Section: Utilização Do Gesso X Disponibilidade De Alumínio No Solounclassified
“…A exploração, através da mineração, destas formações acaba gerando uma elevada quantidade de subprodutos, que sem uma real utilização tornam-se resíduos. Visando um consumo consciente, é de extrema importância encontrar finalidades a estes (Theodoro, et al, 2013).…”
Section: A Rochagemunclassified